Self-Organization of Condensed Matter in Fluctuating Environment - Kharchenko, D.O. (Успехи физики металлов, 2005)
A synergetic conception of plastic deformation is presented allowing for the defects’ interplay resulting in a phase transition. A qualitative-reconstruction pattern of imperfect condensed-matter structure in the presence of fluctuations in both 0-dimensional and distributed (extended) systems is considered. As shown, the system undergoes the reversible phase transitions under the increasing intensity of fluctuations, diffusion constituent and deformation-type external parameters. Within the framework of the synergetic approach based on the Lorenz system, a pattern of explosive crystallization is shown to be scripting the same way as the avalanches formation. The relationships are set between the exponent of a size distribution of avalanches, the fractal dimension of a phase space, characteristics of noise, the number of governing equations, the dynamical exponent, and the non-additivity parameter. As shown, the regime of self-organized criticality is associated with an anomalous diffusion processes.